Romantyczny model retoryki i nauki o stylu. Przegląd problematyki - Bogołębska, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 1998)
The article deals with the phenomenon of anti-rhetorical polemics in the Romanticism - its causes and consequences. In the Romanticism the criticism of the rhetorical theory of rhetoric was accompanied by an anti-normative attitude. The aesthetic standards accepted by the Romanticists were the explanation for this somehow dual rebellion. The essay is an attempt to recreate the Romantic conceptions of style and the science of style. Research shows that the nineteenth century did not mean a complete rejection of rhetoric, but only a reduction in the theoretical issues. The didactic methods of grammar school and university seem to confirm the situation.